A hydroxamic-acid-containing nucleoside inhibits DNA repair nuclease SNM1A. Issue 35 (5th August 2019) - Doherty, William; Dürr, Eva-Maria; Baddock, Hannah T.; Lee, Sook Y.; McHugh, Peter J.; Brown, Tom; Senge, Mathias O.; Scanlan, Eoin M.; McGouran, Joanna F.
Abstract : Modified thymidine incorporating zinc-binding pharmacophores offers a novel approach for inhibitor development of SNM1A using rationally designed nucleoside derived inhibitors. Abstract : Nine modified nucleosides, incorporating zinc-binding pharmacophores, have been synthesised and evaluated as inhibitors of the DNA repair nuclease SNM1A. The series included oxyamides, hydroxamic acids, hydroxamates, a hydrazide, a squarate ester and a squaramide. A hydroxamic acid-derived nucleoside inhibited the enzyme, offering a novel approach for potential therapeutic development through the use of rationally designed nucleoside derived inhibitors.